Publishing practices in non-recommended journals in thoracic field - implications for scientific integrity - Fahmi H. Kakamad; Berun A. Abdulla; Farman J. Ahmed; Dana HB. Mohammed Saeed; Harem K. Ahmed; Yousif M. Mahmood; Shvan H. Mohammed; Hiwa O. Abdullah; Meer M. Abdulkarim; Hawkar A. Nasralla; Ayman M. Mustafa; Kaiwan Talib Saeed (Advancements in Health Research, 2026)
Publishing in non-recommended journals (NRJs) threatens scientific integrity by prioritizing financial gain over rigorous peer review, editorial transparency, and research quality. Although documented in several medical fields, NRJs in thoracic research remain underexplored. This study aimed to assess the prevalence, geographic distribution, and key characteristics of NRJs in the thoracic field. A cross-sectional analysis was conducted using the Kscien List to identify thoracic NRJs. Journals were included if their scope or title referenced thoracic disciplines. Data were collected on publication practices, article processing charges, editorial leadership, indexing status, and the geographic distribution of corresponding authors and editorial board members. Descriptive statistics were used to summarize findings. Seventy-five NRJs were identified, publishing 7,656 articles with 3,098 corresponding authors from 82 countries. Authorship was concentrated in the United States (21.76%) and India (15.36%). Editorial boards included 1,912 members, 70.3% from eight countries, led by the United States (29.39%). Most journals (84.0%) charged fees, with 29.4% exceeding USD 2,000. Poor editorial practices were common, and none were indexed in Web of Science, Scopus, or DOAJ. The presence of numerous NRJs represents a critical and often overlooked threat to the integrity of thoracic research.